Access to justice for victims of corporate environmental degradation in Zambia : the case for public interest litigation - Maziwisa, Michelle (University of Pretoria, 2025)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.